Paleomagnetic studies on the late Ediacaran – Early Cambrian Puncoviscana and the late Cambrian Campanario formations, NW Argentina: New paleogeographic constraints for the Pampia terrane. (October 2016) - Franceschinis, Pablo R.; Rapalini, Augusto E.; Escayola, Monica P.; Luppo, Tomás
Abstract: A magnetofabric and paleomagnetic study was carried out in the Late Ediacaran – Early Cambrian Puncoviscana and the early Late Cambrian Campanario formations, exposed in Santa Victoria Oeste, in northwestern Argentina. Ten sites (93 samples) were located in tuffs and volcanic sills interbedded in the Puncoviscana Formation, one of which had been dated at 537 ± 0.9 Ma. On the other hand, 42 samples were collected at three sites from red to purple sandstones of the Campanario Formation. The analysis of anisotropy of magnetic susceptibility (AMS) allowed to recognize a pre-Andean fabric in both formations indicating that it is previous to the Andean cycle. In the paleomagnetic study reliable magnetic components were isolated in only two sites of the Puncoviscana formation whose virtual geomagnetic poles (VGPs) are close to but do not coincide with the apparent polar wander path of Río de la Plata craton – Gondwana for the late Neoproterozoic – Cambrian. A new paleomagnetic pole (18.2°S, 358.8°W, K: 27.9; A95: 3.9) was computed for the Campanario formation which is close to but does not coincide with those obtained in other locations for this unit and were considered anomalous respect to the expected position in the Gondwana path. The pole presented here is closer to the apparent polar wander path of Gondwana for the Late Cambrian-Early Ordovician suggesting two possible interpretations; the presence of different amounts of Andean tectonic rotations between different sampling locations of the Campanario Formation or the recording of a rapid Pampia dextral displacement along the Rio de la Plata craton margin in Cambrian times. Graphical abstract: Highlights: First virtual geomagnetic poles for the late Ediacaran – Early Cambrian Puncoviscana Formation in Argentina are presented. A new pole for the late Cambrian Campanario Formation is not consistent with the most accepted Gondwana reference poles. Whether pole disagreements are due to Early Paleozoic displacement of Pampia or Andean local rotations remain unsolved.